The Rise of the Roguelite: Inside a Gaming Phenomenon, edited by James Cartlidge (CRC Press, 2025).: Book review - Matencio Durán, David (Eludamos: Journal for Computer Game Culture, 2025)
A review of James Cartlidge’s edited volume, The Rise of the Roguelite: Inside a Gaming Phenomenon. Published by CRC Press, 2025. ISBN: 978-1-00341-547-3, 200 pages.